IMPLEMENTASI FUNGSI DEBOUNCE PADA APLIKASI DETEKSI CUACA BERBASIS WEB - Muhamad Ahyar Yogi Wibisono; Hardika Khusnuliawati; Astri Charolina (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2024)
Independent Study Program Certified Independent Campus is an official program released by the Ministry of Education, Culture, Research, and Technology (Kemendikbud-Ristek) aims to give opportunities for students to study outside of their study program through internships, independent projects, research, and professional training. Web-based weather detector applications are very useful tools in everyday life. With accurate weather information, users can plan their activities better. A common problem with search applications is that they make repeated requests to the server every time the user types something into the search menu. This can overload the server and slow down response times. In overcoming this problem, the debounce feature is used. Debounce is a function used to control delays based on a predetermined time. The research method used the SUS method by providing several questionnaires consisting of 10 questions related to the Weather App application to 33 respondents. The results show the Weather App usability value of 82.65 or has a usability grade of A which is quite good. However, there must be shortcomings in the weather app application due to the limitations of the public API.